Comparative in-silico analysis of vitexin and orientin as potential antiphotoaging agents against MMP enzymes - Nyunda, Ricky Putra Banyim; Wiantini, Ni Made Rita; Susanti, Ni Made Pitri; Laksmiani, Ni Putu Linda (Pharmacy Reports, 2023)
Photoaging, a result of excessive UV exposure, increases ROS production and collagen degradation by MMPs, causing skin wrinkles and roughness. This study explores the potential of vitexin and orientin as natural antiphotoaging agents through in-silico molecular docking, comparing their efficacy against retinol in inhibiting MMP-1, MMP-3, and MMP-9 enzymes involved in photoaging. The research utilized Hyperchem 8 for compound optimization, Chimera 1.11 for target protein preparation, and AutodockTools 1.5.6 for docking analysis. Results demonstrated that vitexin and orientin exhibit stronger affinity towards MMP-1, MMP-3, and MMP-9, indicated by more negative binding energies than retinol. Their interaction with the MMP enzymes, characterized by specific hydrogen bonds with key amino acid residues, suggests a potent inhibitory effect. This affinity indicates vitexin and orientin’s potential as effective antiphotoaging agents, providing a basis for further exploration in skin care applications.